Revitalisasi Pendidikan Agama Islam di Perguruan Tinggi: Membangun Mahasiswa Yang Intelektual dan Spiritual - Wakib Kurniawan; Titik Sriwahyuni; Bahrudin Yusuf Zen (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Revitalization of Islamic Religious Education (PAI) in higher education has become a strategic urgency in responding to the challenges of globalization, secularization of education, and the crisis of students' spiritual identity. This article aims to examine new approaches in PAI learning that are able to integrate students' intellectual and spiritual intelligence. Using a descriptive qualitative approach through literature study, this study identifies the need for curriculum transformation, contextual learning methods, and the role of lecturers as value facilitators. The results of the study indicate that PAI revitalization must include a transdisciplinary approach, the use of digital technology, and the integration of religious moderation values. These efforts will shape the character of students who are not only intellectually critical but also spiritually strong. This study provides theoretical and practical contributions to the development of PAI curriculum at the higher education level.